The Effect of the Prompt Removal of Inflorescence-Infected Plants and Early Debudding of Inflorescences on the Control of Xanthomonas Wilt of Banana - Blomme, G.; Turyagyenda, L.F.; Mukasa, H.; Ssekiwoko, F.; Mpiira, S.; Eden-Green, S. (ISHS Acta Horticulturae, 2007)
Xanthomonas wilt of banana, caused by Xanthomonas campestris pv. musacearum, is an important constraint to banana production in Uganda. Different strategies to control the disease were investigated in an attempt to identify those methods that could be used by small farmers in East Africa. The effect of removing pseudostems showing early and late symptoms of inflorescence infection on the spread of the disease in ‘Kayinja’ (syn. ‘Pisang Awak’, ABB genome) was studied. Suckers of ‘Kayinja’ did not become infected when pseudostems derived from the same mat were removed at an early stage of inflorescence infection. In addition, the results of experiments to determine the effectiveness of bagging and debudding inflorescences at different stages to prevent insect-borne infection are reported. This research was undertaken using ‘Kayinja’, mixed plantings of East African highland cultivars (AAA) and high-yielding exotic/improved cultivars in farmers’ fields. ‘Kayinja’ was the most susceptible cultivar to floral infection, followed by the East African highland cultivars. Exotic/improved cultivars had the lowest number of infections. Lower numbers of floral infections may be attributed to the persistence of male flowers and bracts. No flower infection was observed on plants that were debudded immediately after the formation of the last cluster and on those that were bagged until the formation of the last cluster and debudded right after. However, plants that were bagged until the formation of the last hand, but not debudded, or debudded after 2 weeks or more, showed high levels of inflorescence infection. This indicates that insect-vector transmission occurs only via the male parts of the inflorescence. Prompt removal of the whole pseudostems showing symptoms of early inflorescence infection and early debudding are simple, cheap, easily applicable and highly effective methods for controlling Xanthomonas wilt. Results of a cost-benefit analysis of control options are discussed.
Keywords: Banana; Xanthomonas Wilt; Inflorescence-Infected Plants; Debudding